An Examination of the Latent Constructs in Risk Tools for Individuals Who Sexually Offend: Applying Multidimensional Item Response Theory to the Static-2002R. (June 2023) - Brouillette-Alarie, Sébastien; Lee, Seung C.; Longpré, Nicholas; Babchishin, Kelly M.
Multidimensional item response theory (MIRT) was used to study the construct validity of the Static-2002R, an actuarial scale for the assessment of reoffending among adult men who sexually offended. Using a sample of 2, 569 individuals with a history of sexual crime, exploratory factor analysis (EFA) extracted three factors: Persistence/Paraphilia, General Criminality, and Youthful Stranger Aggression. MIRT confirmed the factor structure identified in the EFA model and provided item-level data on discrimination and difficulty. All Static-2002R items showed moderate to very high discrimination and covered a wide range of risk levels (i.e., difficulty). MIRT analyses attested to the construct validity of the scale, as no items were identified as problematic and the resulting factor structure was consistent with that of earlier studies. Considering the stability of results pertaining to the factor structure of the Static-2002R and the advantages of dimensional scoring, we recommend the integration of dimensional scores in the scale.